2021
DOI: 10.1039/d1dt01839f
|View full text |Cite
|
Sign up to set email alerts
|

Reversible single-crystal to single-crystal phase transformation between a new Werner clathrate and its apohost

Abstract: A new Werner complex exhibits reversible transformation between apohost and host–guest phase induced by nitrobenzene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…It has been reported that nonporous molecular solids, e.g., bishydrazones, can distinguish one isomer from a mixture of C8 aromatics, highlighting the significance of phase transformations and conformational flexibility in adapting host cavities to fit guest molecules . We herein report the C8 aromatic inclusion properties of a hitherto unstudied molecular compound, 4-(1 H -1,2,4-triazol-1-yl)-phenyl-1 H -benzo­[de]­isoquinoline-1,3­(2 H )-dione, TPBD , which was prepared by cocrystal-controlled solid-state synthesis (solvent-drop grinding, SDG, followed by heating). TPBD’s selection is rooted in its inherent structural features and the aforementioned studies on molecular compounds such as Werner complexes. The studies of Werner clathrates highlight that molecular compounds comprising aromatic rings and conformational diversity can form host–guest complexes with C8 isomers.…”
Section: Introductionmentioning
confidence: 92%
“…It has been reported that nonporous molecular solids, e.g., bishydrazones, can distinguish one isomer from a mixture of C8 aromatics, highlighting the significance of phase transformations and conformational flexibility in adapting host cavities to fit guest molecules . We herein report the C8 aromatic inclusion properties of a hitherto unstudied molecular compound, 4-(1 H -1,2,4-triazol-1-yl)-phenyl-1 H -benzo­[de]­isoquinoline-1,3­(2 H )-dione, TPBD , which was prepared by cocrystal-controlled solid-state synthesis (solvent-drop grinding, SDG, followed by heating). TPBD’s selection is rooted in its inherent structural features and the aforementioned studies on molecular compounds such as Werner complexes. The studies of Werner clathrates highlight that molecular compounds comprising aromatic rings and conformational diversity can form host–guest complexes with C8 isomers.…”
Section: Introductionmentioning
confidence: 92%
“…48 In this context, we have recently explored guest-induced structural transformations of Werner complexes and termed them as s̲ witching a̲ dsorbent m̲ olecular m̲ aterials (SAMMs). 49,50 To the best of our knowledge, the first phase switching transformation among FMOMs was observed in a SAMM, the Werner complex [Co(4-ethylpyridine) 4 (NCS) 2 ] (SAMM-1-Co-NCS), dating back to 1969. 51 The gas/vapor sorption properties of other Werner complexes remains understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal engineering , is about understanding intermolecular interactions in single-component and multicomponent molecular crystals. , Multicomponent crystals can be synthesized by the supramolecular synthon approach and shape and size mimicry. , Cocrystals, salts, solvates, cocrystal salts, salt solvates, cocrystal solvates, and cocrystal salt solvates are characterized under the category of multicomponent crystals. ,, If water is occupied in the crystalline lattice, it is called hydrate or hydrated crystals. If the asymmetric unit contains at least one solvent molecule along with the API and/or given molecule, the crystal is called a solvate crystal. In another scenario, multicomponent crystalline solids can be described as host–guest complexes, clathrates, and pseudo polymorphs. The phenomenon of the host–guest system has a fundamental importance in pharmaceutical drug development, so the study of model compounds well in advance could be advantageous. Recently, Desiraju’s group designed a host–guest system of hydrated 3,5-dihydroxybenzoic acid where water was used as a design element .…”
Section: Introductionmentioning
confidence: 99%
“… 14 21 If the asymmetric unit contains at least one solvent molecule along with the API and/or given molecule, the crystal is called a solvate crystal. In another scenario, multicomponent crystalline solids can be described as host–guest complexes, 22 clathrates, 23 and pseudo polymorphs. 24 27 The phenomenon of the host–guest system has a fundamental importance in pharmaceutical drug development, 28 so the study of model compounds well in advance could be advantageous.…”
Section: Introductionmentioning
confidence: 99%